Nanoplastics and Microplastics in Agricultural Systems: Effects on Plants and Implications for Human Consumption - Tarcisio Wolff Leal; Gabriel Tochetto; Sayonara Vanessa de Medeiros Lima; Patricia Viera de Oliveira; Henrico Junior Schossler; Carlos Rafael Silva de Oliveira; Afonso Henrique da Silva Júnior (Microplastics)
Nanoplastics and microplastics in agricultural systems have raised significant concerns due to their effects on plant health and potential risks to human consumption. This review examined these pollutants’ origins, behavior, and impacts in agricultural environments, emphasizing their primary contamination pathways, such as irrigation, plastic mulching, and sewage sludge application. It explored the transport, accumulation, and interactions of these particles in the soil, including their ability to adsorb other contaminants like pesticides and heavy metals. The effects on plant physiology and potential toxicity were highlighted, along with the implications for food quality and safety. Chronic exposure to these pollutants through the food chain posed notable health concerns for humans, emphasizing the urgency of addressing this issue. Research gaps, such as the toxicokinetics of nanoplastics and microplastics in plants and humans, were identified, underscoring the need for further investigation. The review also presented mitigation strategies, including improved waste management and the development of sustainable agricultural practices.